Multiculturalism: Identity, Language and Culture in Zadie Smith’s White Teeth - Lateef Alnajm, Alaa (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims at examining the specific meaning of multiculturalism, identity, language, and culture in Zadie Smith’s White, her debut novel. Smith depicts a clear picture of the multicultural society of Britain in general and London in particular. However, the paper studies the ways in which Smith’s novel transcends and promotes the limitations of black women. The study investigates how multicultural society of Britain is drawn through the role of each character in the novel; therefore, it shows the complex construction of identity created by Smith to illustrate the relationship built by different races, languages, and religions. The paper also examines how Zadie Smith in her use of language integrates the linguistic process that existed in the intercultural experiences of both the characters and the author herself. Smith highlights the reality of living in a postmodern world; she also makes her; characters interact with each other as they live exactly the real meaning of life. Therefore. her runway success pushed the young writer to the central mainstream of attention.